Code Switching and Code Mixing in TikTok Comment Columns and Its Implications for Indonesian Language Learning at High Schools - Putri, Melani Regita; Sulistiyono, Yunus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this research is to analyze the forms of code switching and code mixing in TikTok social media account comments, analyze the forms of slang in TikTok social media account comments, analyze the implications of code switching and code mixing for Indonesian language learning. This type of research is descriptive qualitative research. The data studied in this research consists of TikTok social media user comments that contain code switching, code mixing, and slang. The object of this research is TikTok social media comments. Meanwhile, the subjects of this research are code switching, code mixing, and slang. The data collection techniques used in this research are content analysis and documentation. The steps taken to collect data are as follows; 1). Read carefully the comments of tiktok social media users, 2) identify and record comment quotes, 3) classify the data that has been identified in groups of code switching, mixing, code and slang. In addition to taking notes, researchers also conduct documentation by screenshotting the data that has been found. The data analysis technique in this research uses descriptive qualitative. The results of data analysis are presented in the form of narrative descriptions and explanations regarding code switching, code mixing, and slang under study. In this study researchers used 20 data that had been analyzed, of these 20 data divided into 10 data were the use of code switching and code mixing and 10 data were the use of slang language in the TikTok social media comment column.